Does New Mental Health Legislation in Victoria, Australia, Advance Human Rights? - Chris Maylea (Harvard FXB Center for Health and Human Rights, 2023)
In introducing the Mental Health and Wellbeing Bill of 2022 into Parliament in Victoria, Australia, the state government claimed that the new legislation "delivers on the vision for rights-based mental health and wellbeing laws." This paper examines the new legislation in light of both local human rights legislation and international human rights law. Drawing primarily on the United Nations Convention on the Rights of Persons with Disabilities and the Victorian Charter of Human Rights and Responsibilities Act of 2006, this paper argues that while the new legislation is not, in fact, rights based, it does represent some rights-related improvements over existing legislation. The paper concludes with a discussion of how rights-based legislation could be applied to the Victorian context, using the latest guidance from the World Health Organization and the United Nations.